2013
DOI: 10.1021/nn404640c
|View full text |Cite
|
Sign up to set email alerts
|

Carbon Nanosheet Frameworks Derived from Peat Moss as High Performance Sodium Ion Battery Anodes

Abstract: We demonstrate that peat moss, a wild plant that covers 3% of the earth's surface, serves as an ideal precursor to create sodium ion battery (NIB) anodes with some of the most attractive electrochemical properties ever reported for carbonaceous materials. By inheriting the unique cellular structure of peat moss leaves, the resultant materials are composed of three-dimensional macroporous interconnected networks of carbon nanosheets (as thin as 60 nm). The peat moss tissue is highly cross-linked, being rich in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

23
632
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 862 publications
(656 citation statements)
references
References 58 publications
23
632
1
Order By: Relevance
“…The CV curves of DC in half cells (Figure 3 a) tested between 0 and 2 V (vs Na + /Na) show a pair of sharp reduction (centered at 0.05 V) and oxidation peaks (centered at 0.25 V), which are consistent with the intercalation and deintercalation of Na + ions into/from the disordered carbon structure. [23][24][25] Very recently, the reversible Na + ion intercalation between graphene layers in partially ordered carbons has been demonstrated by Mitlin's group, [41][42][43] which is similar to our results. In contrast, the CV curves of MG display a rectangular shape between 2 and 4.2 V (vs Na + /Na), indicative of typical EDLC behavior.…”
Section: Communicationsupporting
confidence: 92%
“…The CV curves of DC in half cells (Figure 3 a) tested between 0 and 2 V (vs Na + /Na) show a pair of sharp reduction (centered at 0.05 V) and oxidation peaks (centered at 0.25 V), which are consistent with the intercalation and deintercalation of Na + ions into/from the disordered carbon structure. [23][24][25] Very recently, the reversible Na + ion intercalation between graphene layers in partially ordered carbons has been demonstrated by Mitlin's group, [41][42][43] which is similar to our results. In contrast, the CV curves of MG display a rectangular shape between 2 and 4.2 V (vs Na + /Na), indicative of typical EDLC behavior.…”
Section: Communicationsupporting
confidence: 92%
“…They also confi rmed that the d -spacing between graphene layers is reversibly expanded and contracted upon the de/sodiation based on ex situ XRD analysis, which is indicative of Na intercalation in the hard carbon lattice in the low-voltage plateau region (Figure 10 e). [ 287,302,322 ] The theoretical study performed by Tsai et al in Figure 10 f suggested that the slopevoltage region is attributable to Na adsorption on the defective carbon surface, and the plateau region is responsible for the Na intercalation in the hard carbon lattice. [ 276 ] As a result, the Na storage mechanism can be classifi ed as (i) Na adsorption at defective sites in the slope-voltage region, (ii) Na intercalation in the hard carbon lattice, and (iii) Na-atom adsorption at the pore surface in the plateau region (Figure 10 g).…”
Section: Non-graphitic Carbonmentioning
confidence: 98%
“…Various sources, such as glucose, banana peels, and polyaniline, have been used to produce hard carbon, which delivers high capacities (100 to 200 mAh·g −1 ) and good rate capability. [15][16][17] 18 Another strategy to enhance the electrochemical properties of rGO is chemical decoration by heteroatoms (N, P, B, etc.). The introduced heteroatoms create more defects and change the electronic conductivity of rGO so as to promote Na-ion storage.…”
Section: Introductionmentioning
confidence: 99%